Desarrollo de una aplicación móvil para dispositivos con os android orientada a la identificación de operadoras móviles. - Arias Tandazo, Jayro Michael (2017)
The present work of the titration describes in a practical way and with theoretical foundations the development in stages of a mobile application for the devices with OS Android oriented to the identification of mobile operators with the ability to modify the device contacts presentation, identifying with a label red to mobile operator claro, green to movistar mobile operator and blue to cnt mobile operator. Each stage of development is oriented to a specific objective, starting with the choice of the Android SDK software development interface as the appropriate, an own criteria, able to adapt to the needs and developer knowledge, an algorithm capable of managing, process and compare a web database, with the phonebook stored in the device and in this way provide the user with a tool that allows the savings of economic resources for the connection of voice inter and intra-operators.